Inclusion of feather meal in the diet with reduced protein and amino acids for meat quails (Research, Society and Development, 2020)
The objective was to evaluate the inclusion of feather meal (FM) in diets reduced in crude protein (CP) and amino acids (AA) for meat-type quails. 240 male meat-type quails were used in the phases from 8 to 21 days and 8 to 35 days of age, distributed in a completely randomized design, in a 2 x 3 factorial scheme (two diets: positive control (PC) and negative control (NC) reduced in CP and AA in relation to PC x three levels of inclusion of FM: 0, 5 and 10%), totaling 6 treatments, with 4 repetitions of 10 quails per plot. There was an interaction (P 0.05) of the interaction between the factors, but an effect (P0.05) the carcass variables, except for the thigh + drumstick yield (P